PENGGUNAAN KALIMAT DALAM SURAT KELUAR DINAS KESEHATAN KABUPATEN PELALAWAN - Mutia Anisa; Nursal Hakim; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTUtilization of effective sentence very important in communication. Effective sentence be able to send message by writer or speaker so that listener can accept that message like writer or speaker meant. The problems that writer examines on this research is how utilization sentence out letter in healthy department Pelalawan regency looked by an idea, parallel, economical, coherent, pressure, logical, and variant aspect? This research purpose to descript utilization sentence out letter in healthy department Pelalawan regency looked by an idea, parallel, economical, coherent, pressure, logical, and variant aspect? Qualitative researches with analysis descript method, using gathering documentation technical. Work of documentation technical is collecting letter that become subject for research and then analysis exactly with problem research. Result of this research any 10 sentences it’s not economical utilization sentence, 161 sentences it’s not using pressure aspect, and 165 sentences it’s not using variant aspect. Result of this research indicated the utilization sentence out letter in healthy department Pelalawan Regency not yet effective. This showed by more sentence it’s not economical, not using pressure, and not variant on that letters.Key Word: Effectife Sentence, Out Letter